2004
DOI: 10.1002/mus.20013
|View full text |Cite
|
Sign up to set email alerts
|

Nerve excitability properties in lower‐limb motor axons: Evidence for a length‐dependent gradient

Abstract: In this study, nerve excitability protocols were adapted for lower-limb recordings in 25 healthy subjects to enable comparison of excitability parameters between proximal and distal recording sites of the same nerve and between different nerves. Excitability parameters (stimulus-response curves, strength-duration properties, threshold electrotonus, a current-threshold relationship, and the recovery cycle) were recorded from tibialis anterior, extensor digitorum brevis, and abductor hallucis. Excitability recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 53 publications
6
35
0
Order By: Relevance
“…The threshold changes to polarizing currents in mouse tibial motor axons were smaller than those reported for human tibial nerves (Krishnan et al, 2004) and cat tibial nerves (Moldovan and Krarup, 2004b) but similar to those reported in rat caudal motor nerve (Yang et al, 2000). The comparisons were complicated by the fact that we set the polarization current relative to the 0.2 ms threshold and not relative to 1 ms threshold as in previous studies.…”
Section: A Mouse Model For Threshold Trackingsupporting
confidence: 58%
“…The threshold changes to polarizing currents in mouse tibial motor axons were smaller than those reported for human tibial nerves (Krishnan et al, 2004) and cat tibial nerves (Moldovan and Krarup, 2004b) but similar to those reported in rat caudal motor nerve (Yang et al, 2000). The comparisons were complicated by the fact that we set the polarization current relative to the 0.2 ms threshold and not relative to 1 ms threshold as in previous studies.…”
Section: A Mouse Model For Threshold Trackingsupporting
confidence: 58%
“…3,18 In this method, a constant target MEP amplitude is tracked online by a test stimulus using different conditioning-test paradigms. Although threshold tracking has been validated in electrical studies of peripheral ax-ons in healthy controls 23,24,30,35 and in the investigation of disease pathophysiology in a wide array of neurological disorders, 5,6,8,[25][26][27][28]31,33 limited data exist for the application of threshold tracking to TMS to study cortical excitability. Consequently, the aim of the present study was to determine the adaptability of threshold tracking to TMS techniques to investigate the processes of intracortical inhibition and facilitation.…”
mentioning
confidence: 99%
“…17 In this context, previous studies have demonstrated that even at the same site of the same nerve, the excitability properties of motor axons can differ significantly according to the muscles that they innervate. 8,13,22 Conversely, it has also been reported that axonal excitability in the same muscle recording can …”
Section: Discussionmentioning
confidence: 99%